Geothermal resources in the northern Harrat Rahat volcanic field, Saudi Arabia: A drilling and field data assessment - Bischoff, Alan; Bankher, Khalid A.; Alashi, Ehab A.; Arola, Teppo; Brinji, Haitham S.; Nemeth, Karoly; Martinkauppi, Annu; Jabrte, Akram H.; Kortunov, Evgenii; Alzahrani, Ibrahim S.; Martinkauppi, Ilkka; Melibari, Rami A. (Elsevier Ltd, 2026)
Geothermal energy exploration is gaining momentum in the Kingdom of Saudi Arabia. Here, we present the findings of a geothermal exploration programme conducted in the northern Harrat Rahat volcanic field. Our investigations highlight the geological events, volcanological characteristics, and structural patterns that influence the formation and distribution of geothermal resources in the area. The main objective was to identify conventional geothermal systems suitable for commercial electricity generation and secondarily estimate the potential of unconventional geothermal systems. Key findings include the recording of a modest conduction-dominated geothermal gradient of up to 23.6 degrees C/km. Although no active geothermal reservoirs were found (maximum measured temperature of 54 degrees C), the mineral paragenesis, including chlorite, epidote, and rhodonite associated with hydraulic brecciation, indicates that fossil high-temperature (similar to 300 degrees C) hydrothermal systems were once working at shallow depths (<1000 m) beneath the Rahat. Accounting the uncertainties of our preliminary study, we estimate that unconventional geothermal systems could potentially achieve MWe-scale capacities if built at depths of nearly 6 km. The results of our research provide valuable insights into the geothermal potential of the Rahat volcanic field and contribute to expanding the understanding of geothermal resources in Saudi Arabia and similar geological settings worldwide.